Advanced quantum mechanics : A practical guide - Nazarov, Yuli V.; Danon, Jeroen, 1977- (Cambridge : Cambridge University Press, 2013)
'An accessible introduction to advanced quantum theory, this graduate-level textbook focuses on its practical applications rather than mathematical technicalities. It treats real-life examples, from topics ranging from quantum transport to nanotechnology, to equip students with a toolbox of theoretical techniques'--
Elementary quantum mechanics -- Identical particles -- Second quantization -- Magnetism -- Superconductivity -- Superfluidity -- Classical fields -- Quantization of fields -- Radiation and matter -- Coherent states -- Dissipative quantum mechanics -- Transitions and dissipation -- Relativistic quantum mechanics.
Includes index.
Keywords: Quantum theory -- Textbooks